Best proximity points of cyclic $φ$-contractions in ordered metric spaces - Derafshpour, Majid; Rezapour, Shahram; Shahzad, Naseer (Topological Methods in Nonlinear Analysis, 2011)
In this paper, we shall give some results about best proximity points of cyclic $φ$-contractions in ordered metric spaces. These results generalize some known results.